Heat and mass transfer in anisotropic heat-protective composite materials under aerodynamic heating - E. L. Kuznetsova; A. A. Orekhov; V. F. Formalev (Учёные записки Казанского университета: Серия Физико-математические науки, 2024)
This article presents a mathematical model of heat and mass transfer in anisotropic heat-protective composite materials (HPCM) during phase transformations of HPCM binders with the formation of a porous coke residue and pyrolysis gases filtering through the residue to the outer boundary. Using known binder decomposition and nonlinear filtration laws for random HPCMs, the model determines the velocity and coordinates of the two-dimensional HPCM binder decomposition zone, as well as the two-dimensional regions of the porous-gas residue and the initial phase, which are unsteadily separated by a moving zone of binder decomposition. In the newly formed porous-gas region, a two-dimensional unsteady problem of anisotropic heat conduction was solved taking into account nonlinear anisotropic gas filtering. In the initial region unaffected by the binder decomposition, a two-dimensional unsteady problem of anisotropic heat conduction was solved. The mass and linear velocities of the binder decomposition (pyrolysis) zone were calculated from Stefan conditions for heat flow and temperature continuity. The complex model was solved by the previously developed effective and absolutely stable method of alternating directions with extrapolation. New results wereobtained and discussed.